Reality of Kawasaki disease epidemiology - Gi Beom Kim (Korean Pediatric Society, 2019)
Epidemiologic studies of Kawasaki disease (KD) have shown a new pattern or change of its occurrence suggestive of its pathophysiology or risk factors from the first patient with KD reported in 1961. The incidence of KD in Northeast Asian countries including Japan, South Korea, China, and Taiwan is 10-30 times higher than that in the United States and Europe. Knowing the true epidemiology of KD in each country and the availability of publications of KD epidemiology also could benefit general health care providers and general population. This would enable the early detection and treatment of KD, ultimately reducing the incidence of coronary artery complications and mortality. Therefore, efforts to investigate the true epidemiology of KD should be continued in every country using a questionnaire survey, National Health Insurance system data, or combined methods depending on each country's medical environment to ensure high-quality care of patients with KD.